The Effect of Banjar Language-Based Education on Hypertension Knowledge Level - Raihana Rabiatul Adawiyah; Rian Tasalim; Bagus Rahmat Santoso (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Uncontrolled hypertension makes the results worse. Knowledge of hypertension is a strong predictor of preventing complications. Increased knowledge can be provided through education. Language that is difficult for the public to understand when delivering information affects the success of education. So that the provision of education needs to pay attention to cultural aspects, one of which is the local language used by the community. This study aims to identify the respondent's characteristics of the history of hypertension, identify the influence before and after the provision of banjar language-based education on increasing knowledge of hypertension. The type of research design is Pre-Experimental one group pretest-posttest. The sample in this study amounted to 12 people. Sampling using total sampling technique. Data collection using the CAHE questionnaire with data analysis using the Wilcoxon statistical test. The results showed that before the intervention was given the level of knowledge was mostly not good 50.0% after being given the intervention there was an increase in knowledge of hypertension to 83.3%. Wilcoxon test results show that the value of = 0.002 < 0.05 so that H1 is accepted. The conclusion that nurses act as educators can make banjar language-based education one of the methods of health education in an effort to increase knowledge in hypertension sufferers